Muhammad Abduh's Criticism of Gabriel Hanotaux's Thought in the Book Islam Bainal Ilmi wal Madaniyah - Wahyudi Rahman (Islamic Thought Review, 2023)
This article examines Muhammad Abduh's criticism of Gabriel Hanotaux's thoughts, as stated in his book Islam Bainal Ilmi Wal Madaniyah. The type of research used is literature, with a figure study approach. The results showed that Abduh disagreed with Hanotaux in 6 cases. First, regarding progress, only the European Christian Aryan ethnic group possessed it. According to Abduh, the advancement of the rights of all ethnicities and the attribution of Aryan ethnicity to Christianity is not appropriate. Second, Hanotaux wrongly considers Islam a fatalist religion and Christianity a religion that has free will in its destiny. Third, regarding the social reality of Muslims, Abduh has the same views as Hanotaux and is self-critical of the situation of Muslims. Fourth, on the theme of colonial politics, Abduh criticized Hanotaux, who argued that this was purely out of religious interests. Fifth, in the theme of secularization, Hanotaux mixes state political affairs with religion to completely separate them, while Abduh believes that the two can't be separated; all that can be done is to divide tasks and areas of authority between politics and religion.